The efficiency analysis methods of decontamination of Fukushima Prefecture territory (Japan) - Dmitriy V. Aron (Статистика и экономика)
The article deals with the problems of radiological and economic efficiency of decontamination procedures as a measure of eliminating radioactive contamination in scarcely populated residential areas of Fukushima Prefecture (Japan).The objective of the research was to identify and compare with officially declared results the real effects of the decontamination measures on improving the radiation situation and reducing radiation doses for the population in Fukushima region. There was another objective of estimating the expected decontamination expenditure for these territories and the economic efficiency of this measure in accordance with the official international recommendations. The results of such kind of survey for Japan and actual values of the prevented doses due to the decontamination have not been published before. The key objective of this research was to assess the need for decontamination in sparsely populated areas of Fukushima Prefecture taking into account relatively low radiation background in these areas and significant associated financial losses.The initial data for the research have been taken from the Environment Ministry (Japan) reports on the restoration progress in the NPP area. The data on the current radiation situation in Japan have been taken from the Japan Nuclear Regulatory Commission Internet publications. A mathematical modeling of the radiation situation in remediation territories near Fukushima-1 NPP was carried out in the research taking into account the simultaneous impact of several natural and anthropogenic factors. This mathematical model is described in the article. Some empirical dependencies obtained after the Chernobyl accident were also used in it.As the results of the research, the estimated values of actual, predicted and prevented by the decontamination and the resettlement measures doses to residents in one specific Fukushima prefecture municipality were presented.The total and average financial costs per unit of prevented exposure dose for different emergency measures scenarios were estimated, including longterm and short-term evacuation and decontamination. The estimated values of the decontamination and the resettlement effectiveness were presented based on the comparison of the public costs and benefits.The author goes on argue that radiological effectiveness of the decontamination measures was very low. He noted that the measures were inconsistent with the principles of cost optimization in the world radiation protection standards. However, at the same time, the decontamination measures made it possible to prevent possible high costs to the government, and some positive social effects were finally achieved.